If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1x + 3) = -4(-1x + -12) Reorder the terms: 2(3 + -1x) = -4(-1x + -12) (3 * 2 + -1x * 2) = -4(-1x + -12) (6 + -2x) = -4(-1x + -12) Reorder the terms: 6 + -2x = -4(-12 + -1x) 6 + -2x = (-12 * -4 + -1x * -4) 6 + -2x = (48 + 4x) Solving 6 + -2x = 48 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -2x + -4x = 48 + 4x + -4x Combine like terms: -2x + -4x = -6x 6 + -6x = 48 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -6x = 48 + 0 6 + -6x = 48 Add '-6' to each side of the equation. 6 + -6 + -6x = 48 + -6 Combine like terms: 6 + -6 = 0 0 + -6x = 48 + -6 -6x = 48 + -6 Combine like terms: 48 + -6 = 42 -6x = 42 Divide each side by '-6'. x = -7 Simplifying x = -7
| 500-20+30-10-5=100 | | x^7/x^9 | | 3(2x-4)+5=5x+2 | | 105x+9.50=14.75x | | 9/14-9/14 | | 20-y=14 | | 2q-6= | | 2x=(x+10) | | 12x^2-24x-18=0 | | -5-y=14 | | (a+b)x^2+(a+b)x-20(a+b)= | | (x+25)=x | | -y=-3x+6 | | 6(2x^3-4x-3)=0 | | 3x+2x+2x+4+3-9=75 | | 7x-9y=-1 | | -x^3+x^2-2x=0 | | -3(x-2)=9(x-6) | | 16v^3-25v= | | (x+25)=(x+10) | | 13x+21= | | 8b^3+1= | | 50x+75=225 | | .5(5-x)=2.25 | | 4/3*3.14*12^3 | | X^2+80x=-900 | | X^3x^2+2x=0 | | 0.2x-0.6=0.1x+7 | | 1x1/8 | | Log(3x+7)=5 | | 3t+12-4= | | 1.4+0.1x=0.8 |